"I Showed You What I Thought Was Appropriate": Reflections on Longitudinal Ethnographic Research and the Performativity of Dutch Gang Life. Issue 1 (1st June 2021) - Roks, Robert A.
Abstract: This article highlights some aspects of doing longitudinal ethnography in criminology. By zooming in and reflecting on some of the key moments and methodological choices made over the course of more than 15 years of fieldwork among members of a Dutch gang, this article illustrates that relations with informants have the potential to strengthen over time, but that building rapport and trust with (active) offenders is not necessarily a linear process. In addition to voicing the emotional and evocative aspects of these methodological deliberations, this "true confession" is meant to spark some more debate on how longitudinal fieldwork in criminology impacts field relations by critically examining not only the performativity of informants, but also of researchers.